PRODUCTION OF RECOMBINANT Α-AMYLASE BMAN1 WITH AND WITHOUT MUTATIONS IN ESCHERICHIA COLI ARCTICEXPRESS (DE3) FOR STUDYING THE ROLE OF CATALYTIC RESIDUES OF BMAN1 - ZUNIA ROMANSYAH AKHWAN NIM:20516005,
α-Amylase is one of enzymes that hydrolized the internal α-1,4-glycosidic linkages of starch. This enzyme is classified into Glycoside Hydrolase (GH13) family. Enzyme in this family has unique conserved sequence region of catalytic residues. Several researches reported that catalytic residue of this enzyme are comprised of one glutamate and two aspartates. One of the bacteria that produce α-amylase is Bacillus megaterium NL3. α-Amylase from this bacteria has aberrant catalytic residues. Two aspartates are not at conserved region. However, glutamate is at conserved region Therefore, it could be hypothesized that there are other amino acid which contribute to catalysis. In this research, residues that play a role in catalysis were studied by site-directed mutagenesis strategy. Therefore, production of recombinant α-amylase Bacillus megaterium NL3 (BmaN1) with and without mutations in soluble fraction is needed. The purpose of this research are to produce BmaN1 with and without mutation in Escherichia coli ArcticExpress (DE3) and also purify and determine the activity of BmaN1 with and without mutation. Mutants in this research are Glu231Gln, His294Asp, and Lys202Asp. This research is an experimental research consisting of some stages namely production, purification, and biochemical characterization of BmaN1 protein with and without mutation. These protein have been successfully produced in Escherichia coli ArcticExpress (DE3) for 24 hours by using isopropyl β-D-1-thiogalactopyranoside (IPTG) as an inducer. The molecular weight of these protein are ~55 kDa characterized by sodium dodecyl sulfate-poliacrylamide gel electrophoresis (SDS-PAGE). These protein are soluble and insoluble (inclusion bodies). Inclusion bodies are dominant than soluble fraction. The specific activity of BmaN1 on soluble fraction is 0.190 U/mg; Glu231Gln mutant is 0.028 U/mg; His294Asp mutant is 0.145 U/mg; and no enzymatic activity for Lys202Asp mutant. Inclusion bodies were refolded and purified by affinity chromatography Ni-NTA. The spesific activity of refolded BmaN1 is 54.24 U/mg; Glu231Gln mutant is 12.49 U/mg; His294Asp mutant is 25.73 U/mg; and no enzymatic activity for Lys202Asp mutant. The experimental results show that the proteins produced were soluble and inclusion bodies. The solubility of proteins is driven by chaperonin which helps the protein folding properly. The inclusion body is formed by the presence of a hydrophobic site of the BmaN1 structure. The specific activity of soluble and refolded protein is compared. Specific activity of Glu231 residue is consistent because it eliminates the ability of protonation. The specific activity of Lys202 is consistent so it can be considered to play an important role in catalysis. The specific activity His294 is inconsistent. Another approach should be used to prove the role of His 294 in catalysis of BmaN1. Based on these results the residues of Glu231 and Lys202 may play a role in catalysis.